2019
DOI: 10.5577/intdentres.2019.vol9.no2.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of septas in maxillary sinus with cone-beam computed tomography

Abstract: Aim: The aim of the study was to examine the prevalence of maxillary sinus septa (MSS) in a Turkish population, using cone-beam computed tomography (CBCT).
  Methodology: The CBCT images of 350 untreated patients (178 male, 172 female ranging in age between 18 and 65) were included in this study. The presence or absence of MSS was determined in axial, sagittal, and coronal planes by considering gender and side. For statistical evaluation, a chi‐square test was used to determine any differences in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hungerbühler et al stated that edentulous patients had a higher prevalence of MSS partially and fully dentate patients (26). Laçin et al reported that MSS was detected 40.28% of patients in their study (20). Bornstein et al stated that 67% of 212 patients and 57% of 294 maxillary sinuses included MSS (27).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hungerbühler et al stated that edentulous patients had a higher prevalence of MSS partially and fully dentate patients (26). Laçin et al reported that MSS was detected 40.28% of patients in their study (20). Bornstein et al stated that 67% of 212 patients and 57% of 294 maxillary sinuses included MSS (27).…”
Section: Discussionmentioning
confidence: 95%
“…CBCT, panoramic radiography and computed tomography (CT) were used to examine the anatomical structures, pathological entities in the maxillary sinus. CBCT ensures following in radiological examination; i) 3-dimensional examination with lower radiation dose than conventional CT, ii) prevents the superimposition of anatomic structures and pathological entities, iii) provides accurate, detailed visualization and radiological examination (13)(14)(15)(16)(17)(18)(19)(20). The purpose of this study was to evaluate the prevalence of the AP, MSS and relationship between AP and MSS in the maxillary sinus by using CBCT images.…”
Section: Introductionmentioning
confidence: 99%